Maternal Serum Lipid, Estradiol, and Progesterone Levels in Pregnancy, and the Impact of Placental and Hepatic Pathologies - Pecks, U.; Rath, W.; Kleine-Eggebrecht, N.; Maass, N.; Voigt, F.; Goecke, T. W.; Mohaupt, M. G.; Escher, G. (Geburtshilfe und Frauenheilkunde, 2016)
Objective: Lipids and steroid hormones are closely linked. While cholesterol is the substrate for (placental) steroid hormone synthesis, steroid hormones regulate hepatic lipid production. The aim of this study was to quantify circulating steroid hormones and lipid metabolites, and to characterize their interactions in normal and pathological pregnancies with a focus on hepatic and placental pathologies. Methods: A total of 216 serum samples were analyzed. Group A consisted of 32 patients with uncomplicated pregnancies who were analyzed at three different time-points in pregnancy (from the first through the third trimester) and once post partum. Group B consisted of 36 patients (24th to 42nd week of gestation) with pregnancy pathologies (IUGR n = 10, preeclampsia n = 13, HELLP n = 6, intrahepatic cholestasis n = 7) and 31 controls with uncomplicated pregnancies. Steroid profiles including estradiol, progesterone, and dehydroepiandrosterone were measured by GC-MS and compared with lipid concentrations. Results: In Group A, cholesterol and triglycerides correlated positively with estradiol (cholesterol ρ = 0.50, triglycerides ρ = 0.57) and progesterone (ρ = 0.49, ρ = 0.53) and negatively with dehydroepiandrosterone (ρ = − 0.47, ρ = − 0.38). Smoking during pregnancy affected estradiol concentrations, leading to lower levels in the third trimester compared to non-smoking patients (p < 0.05). In Group B, cholesterol levels were found to be lower in IUGR pregnancies and in patients with HELLP syndrome compared to controls (p < 0.05). Steroid hormone concentrations of estradiol (p < 0.05) and progesterone (p < 0.01) were lower in pregnancies with IUGR. Discussion: Lipid and steroid levels were affected most in IUGR pregnancies, while only minor changes in concentrations were observed for other pregnancy-related disorders. Each of the analyzed entities displayed specific changes. However, since the changes were most obvious in pregnancies complicated by IUGR and only minor changes were observed in pregnancies where patients had impaired liver function, our data suggests that placental rather than maternal hepatic function strongly determines lipid and steroid levels in pregnancy.
Keywords: pregnancy; steroids; lipids; IUGR; preeclampsia